Perancangan Sistem Kendali Rumah Pintar Berbasis Arduino - Sitompul, Artaulima; Hotma Pangaribuan (Computer Science and Industrial Engineering, 2024)
The house can act as a place to shelter, rest, gather with family. However, there are times when homeowners often feel worried because they cannot monitor their house thoroughly, especially if it has been abandoned for a long time. Therefore, we need a control device that operates automatically or manually to monitor the condition of the house and can control it remotely. Arduino-Based Smart Home Control". The design of an Arduino-based smart control system that operates automatically or manually with users able to monitor and control remotely using an Android smartphone. The smart home system being built consists of three parts, namely input, processing and output. Process The input consists of PIR, LDR and DHT 11 sensors, then the data from these three sensors is collected by Arduino Mega to be processed into instructions for controlling lights, fan, and buzzers via a 4-channels relay module. The NodeMCU is tasked with sending and reading and controlling lights, fans, and buzzer. Android-based smartphones, the data is read in database storage which is used to display the results of sensor data readings in real time and send data based on controls in the application menu carried out by the user.